Kali LInux CTF blueprints : build, test, and customize your own Capture the Flag challenges across mulitiple platforms designed to be attacked with Kali Linux /: build, test, and customize your own Capture the Flag challenges across mulitiple platforms designed to be attacked with Kali Linux. (2014) - Unknown
No abstract available